Modeling semiconductor export restrictions and the US-China trade conflict - Michael Funke; Adrian Wende (Bank of Finland, Bank of Finland Institute for Emerging Economies (BOFIT), 2022)
The semiconductor industry stands at the center of the intensifying Sino-American trade conflict. Employing a multi-country, multi-sector general equilibrium modeling framework with imperfect competition and heterogeneous firms, we perform qualitative and quantitative analyses of protectionist semiconductor measures. The paper offers two innovations in assessing the macroeconomic impact of current trade restrictions in the semiconductor industry model. First, our model of the semiconductor industry takes into account semiconductor varieties at different technological levels with different substitutability. Second, we model trade restrictions using a novel approach to export bans on semiconductor varieties that is consistent with US policy. Our simulation results suggest that the trade restrictions imposed by the US and its allies consistently lead to a decline in Chinese GDP and welfare. The US also loses, but to a lesser extent. The effect of trade diversion favors the rest of the world. Our simulations further confirm that the US semiconductor industry is likely to be harmed by the restrictions, while China's could be strengthened.
urn:nbn:fi-fe2022112366624
Keywords: F12; F13; F41; 330; International trade; firm heterogeneity; semiconductors; United States; China